Culture and women's land rights on the ground in Uganda. Issue 6 (18th August 2017) - Kabahinda, Jackline
ABSTRACT: In this article, culture as an ideology is contrasted to culture as a reality. The article aims to make a contribution to the study of land tenure rights in Uganda by using a cultural lens to discuss how women's land rights are taking shape as regards changing inheritance practices and improving land use patterns through diversified projects. The evidence from the study villages demonstrates that women's land rights are not only important for women as a category of people, but also for their immediate and extended families, and society at large.